Pengaruh Tes Potensi Akademik Siswa terhadap Prestasi Belajar Matematika - Ganjar Susilo; Tri Astuti Nur'aini (Universitas Indraprasta PGRI, 2018)
The purpose of this study was to determine the effect of students' academic potential tests on mathematics learning achievement. This research was conducted in class XI students of Kutai Kartanegara District Senior High School in Academic Year 2018/2019. The sampling technique uses stratified cluster random sampling which is based on the national average test scores for the mathematics year 2017/2018. In the upper category schools, selected Tenggarong Superior 3 High School, selected middle school category Samboja 1 Public High School and 1 Muara Jawa Public High School, selected lower category school Sangasanga 1 High School. The data analysis technique uses multiple regression analysis. Based on the results of the study it was found that there was an effect of the academic potential test on the mathematics learning achievement of the students of Class XI Public High School in Kutai Kartanegara DistrictTujuan penelitian ini untuk mengetahui pengaruh tes potensi akademik siswa terhadap prestasi belajar matematika. Penelitian ini dilaksanakan pada siswa kelas XI SMA Negeri se-Kabupaten Kutai Kartanegara Tahun Pelajaran 2018/2019. Teknik pengambilan sampel menggunakan stratified cluster random sampling yang berdasarkan nilai rata–rata ujian nasional mata pelajaran matematika tahun pelajaran 2017/2018. Pada sekolah kategori atas, terpilih SMA Negeri 3 Unggulan Tenggarong, sekolah kategori sedang terpilih SMA Negeri 1 Samboja dan SMA Negeri 1 Muara Jawa, sekolah kategori bawah terpilih SMA Negeri 1 Sangasanga. Teknik analisis data menggunakan analisis regresi ganda. Berdasarkan hasil penelitian diperoleh terdapat pengaruh tes potensi akademik dengan prestasi belajar matematika siswa SMA Negeri Kelas XI di Kabupaten Kutai Kartanegara.